Control of p-type conductivity at AlN surfaces by carbon doping. (14th January 2020) - Kishimoto, Katsuhiro; Funato, Mitsuru; Kawakami, Yoichi
Abstract: Carbon doping can form surface p-type conductive layers on AlN with high sheet carrier densities (∼10 13 cm −2 ). Current–voltage measurements indicate carrier injection occurs through the surface conductive layer into AlN, suggesting that the surface conductive layer may act as a p-contact layer for AlN-based materials. Mass spectroscopy reveals that the surface layers with p-type conductivity involve molecular species, including aluminum carbides and carbons, while those without p-type conductivity do not. Carbon-containing layers at AlN surfaces are responsible for surface p-type conduction.